Tracking under-five mortality from 1990 to 2023: Global, regional, and national trends, inequities, and projections toward achieving SDG Target 3.2 by 2030 - Guiying Cao; Jue Liu; Min Liu (PLoS ONE, 2026)
Background In 2015, the UN General Assembly set Sustainable Development Goals (SDGs), in which SDG 3.2 called for all countries to reach an under-5 mortality rate (U5MR) of at least as low as 25 deaths per 1000 livebirths by 2030. As the SDG era enters its final years, it is time to take stock of worldwide trends in U5MRs and progress towards SDG target 3.2. This study aimed to evaluate the time trends in under-5 mortality from 1990 to 2023 with projections towards SDG target 3.2 at the global, regional, and national levels. Methods Annual under-5 deaths and U5MR between 1990 and 2023 at the global, regional, and national levels were collected from a dataset complied by the UN Inter-agency group for Child Mortality Estimation. The percentage changes in under-5 deaths and the estimated annual percentage changes (EAPCs) in U5MRS at the global, regional, and national levels were calculated. Trend extrapolation of the EAPCs was used to estimate the year in which locations with a U5MR > 25 deaths per 1000 live births in 2023 would achieve the SDG 3.2 U5MR target. Results Globally, the number of under-5 deaths decreased by 63.20%, from 12.98 million in 1990 to 4.78 million in 2023, and the U5MR decreased by an average of 3.18% (95% CI: 3.05%, 3.30%) per year from 93.58 deaths per 1000 livebirths in 1990 to 36.72 deaths per 1000 livebirths in 2023. The global U5MR is expected to achieve SDG target 3.2 by 2035. At the regional level, the U5MR decreased significantly in all SDG regions between 1990 and 2023 but remained above SDG target 3.2 in Sub-Saharan Africa (68.82 deaths per 1000 live births) and Central and Southern Asia (33.23 deaths per 1000 live births) in 2023. Sub-Saharan Africa and Central and Southern Asia are projected to reach the SDG 3.2 target by 2055 and 2030, respectively. At the national level, the U5MR decreased significantly in 192 countries and territories between 1990 and 2023 but increased significantly in Dominica (EAPC = 2.38; 95% CI: 2.18, 2.59) and remained stable in 7 countries and territories during this period. Among the 200 countries and territories worldwide, 133 have already met SDG target 3.2, and 9 are expected to do so by 2030. Of the remaining 58 countries that would not achieve SDG target 3.2 by 2030, 22 would meet it between 2031 and 2040, 10 would meet it between 2041 and 2050, and 25 would meet it after 2050, if the average rate of decline from 1990 to 2023 continues; however, the U5MR would deteriorate in Dominica. Conclusions Despite substantial progress in reducing the U5MR worldwide, more than a quarter of countries and territories would not meet SDG target 3.2 by 2030, and nearly half of those countries and territories would meet SDG target 3.2 after 2050. Urgent actions are needed in most regions and countries with high U5MRs, particularly those in sub-Saharan Africa.